Optimization of manganese bioleaching activity and molecular characterization of indigenous heterotrophic bacteria isolated from the sulfuric area - DENAYA ANDRYA PRASIDYA; WAHYU WILOPO; I WAYAN WARMADA; ENDAH RETNANINGRUM (Society for Indonesian Biodiversity, 2019)
Abstract. Prasidya DA, Wilopo W, Warmada IW, Retnaningrum E. 2019. Optimization of manganese bioleaching activity and molecular characterization of indigenous heterotrophic bacteria isolated from the sulfuric area. Biodiversitas 20: 1904-1909.  The present research evaluated the manganese bioleaching potency of a heterotrophic bacteria KB3B1. This bacterial strain has been isolated from sulfuric area located at Ungaran, Middle of Java, Indonesia using modified 9K medium by adding of several organic nutrients. The manganese bioleaching activities of the strain was analysed by applying of varying glycine concentrations (0, 5, 10, 15 mg mL-1) with pyrolusite pulp densities of 0.02 g cm-3 on a rotary shaker at 180 rpm for 18 days incubation. Several parameters, including the growth of bacteria, pH values, the concentration of soluble manganese and cyanide, were investigated at the interval of 3 days. Molecular characteristics of the strain were further analyzed based on 16S rDNA gene sequences. After 15 days, the maximum yield of manganese 16.6% was achieved under the addition of 10 mg mL-1 glycine. This maximum extract obtained was followed by the maximum bacterial growth, pH, and cyanide product of the strain. Phylogenetic analysis showed that the strain was closely related with Bacillus niacini EP89. Besides, the average frequencies of guanine and cytosine (G+C) of the strain was in same range as that of the reference bacteria in the GenBank and Bergey's Manual Systematics of Bacteria.